Mechanistic Insights into the Role of C-Type Lectin Receptor/CARD9 Signaling in Human Antifungal Immunity - Drummond, Rebecca A.; Lionakis, Michail S. (Frontiers in Cellular and Infection Microbiology, 2016)
Human CARD9 deficiency is an autosomal recessive primary immunodeficiency disorder caused by biallelic mutations in the gene CARD9, which encodes a signaling protein that is found downstream of many C-type lectin receptors (CLRs). CLRs encompass a large family of innate recognition receptors, expressed predominantly by myeloid and epithelial cells, which bind fungal carbohydrates and initiate antifungal immune responses. Accordingly, human CARD9 deficiency is associated with the spontaneous development of persistent and severe fungal infections that primarily localize to the skin and subcutaneous tissue, mucosal surfaces and/or central nervous system (CNS). In the last few years, more than 15 missense and nonsense CARD9 mutations have been reported which associate with the development of a wide spectrum of fungal infections caused by a variety of fungal organisms. The mechanisms by which CARD9 provides organ-specific protection against these fungal infections are now emerging. In this review, we summarize recent immunological and clinical advances that have provided significant mechanistic insights into the pathogenesis of human CARD9 deficiency. We also discuss how genetic mutations in CARD9-coupled receptors (Dectin-1, Dectin-2) and CARD9-binding partners (MALT1, BCL10) affect human antifungal immunity relative to CARD9 deficiency, and we highlight major understudied research questions which merit future investigation.